Synthesis of α-Hydroxycarboxylic Acid Anilides via Copper-Catalyzed C–N Coupling of α-Hydroxyamides with Aryl Halides - Li, Zhijie; Wen, Quan; Zhou, Lihong; Deng, Xingmei; Zeng, Qingle (Synthesis, 2015)
The synthesis of highly important α-hydroxycarboxylic acid anilides via copper-catalyzed chemoselective C–N coupling reactions of α-hydroxyamides and aryl halides is described. This highly selective N-arylation process demonstrates wide substrate scope, cost savings and easy operation. In addition, the chirality of l-3-phenyllactamide is preserved during the reaction.
Keywords: α-hydroxycarboxylic acid anilides; copper; cross-coupling; α-hydroxyamides; catalysis; chemoselectivity